2012
DOI: 10.1111/j.1750-3841.2012.02840.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Drying Methods and Storage Time on the Retention of Bioactive Compounds and Antibacterial Activity of Wine Grape Pomace (Pinot Noir and Merlot)

Abstract: The effects of different drying methods (40 °C conventional and vacuum oven, 25 °C ambient air and freeze dry) on the stability of two red wine grape (Pinot Noir, PN and Merlot, M) byproducts, pomace containing skins and seeds (P) and pomace containing skins only (S) were investigated. Freeze dried samples retained the highest bioactive compounds with total phenolic content (TPC) of 21.19-67.74 mg GAE/g d.m., anthocyanin content (ACY) of 0.35-0.76 mg Mal-3-glu/g d.m., DPPH antiradical scavenge activity (ARS) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
59
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 55 publications
11
59
5
Order By: Relevance
“…This phenomena is not unique to apple pomace, and as such different drying methods have been studied in various fruit pomace and vegetables (Bai et al 2013;Choicharoen et al 2009;Constenla et al 2002;de Torres et al 2010;Khanal et al 2010;Raghavan and Orsat 2007;Tseng and Zhao 2012;Yemmireddy et al 2013). Khanal et al (2010) reported that drying grape and blueberry pomaces at lower temperature for longer time (40°C for 72 h) did not cause significant losses in anthocyanins, while higher temperature drying (125°C) for a much shorter time (8 h) led to 70 % reduction.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomena is not unique to apple pomace, and as such different drying methods have been studied in various fruit pomace and vegetables (Bai et al 2013;Choicharoen et al 2009;Constenla et al 2002;de Torres et al 2010;Khanal et al 2010;Raghavan and Orsat 2007;Tseng and Zhao 2012;Yemmireddy et al 2013). Khanal et al (2010) reported that drying grape and blueberry pomaces at lower temperature for longer time (40°C for 72 h) did not cause significant losses in anthocyanins, while higher temperature drying (125°C) for a much shorter time (8 h) led to 70 % reduction.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, drying methods have a significant effect on the quality characteristics of dried fruit, such as phenolic compounds and sensorial properties (Angulo et al, 2007;Tseng & Zhao, 2012). The sun-drying method has the advantage of being more cost-effective than the other drying methods.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have investigated the changes in bioactive compounds (such as total phenolic, anthocyanin, total flavonol) and antiradical scavenging activity of grape skin and pomace by using different drying methods (Larrauri et al, 1997;De Torres et al, 2010;Tseng & Zhao, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, convection drying based on heated air in different designed drying devices (cabinet driers, tunnel driers, fluid-bed driers), vacuum drying, freeze-drying, and alternative methods, such as infrared drying and microwave drying, ensure better process control, shelf-stability and microbiologically safe dried product, with minimal degradation of nutrients and sensory quality 21,22 . Several studies have investigated the effects of different drying methods on the recovery of phenolic compounds from grape pomace [32][33][34][35][36][37] . These studies have compared conventional hot air or vacuum drying with freeze-drying as a more effective drying method for by-products where material is not exposed to high temperatures resulting with preservation of organoleptic and nutritive properties of the products.…”
Section: Introductionmentioning
confidence: 99%